Investigation of the influence of xanthan on mozzarella cheese characteristics focusing on its antimicrobial effect (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study was designed to show the effect of adding different levels of microbial (lab-produced) and commercial xanthan (CX) for 30 days on the sensory, chemical, and microbiological parameters of mozzarella cheese (MC). Materials and Methods: The production of xanthan was done in Garcia–Ochoa’s medium. The sensory evaluation of the examined MC was achieved through a tabulated scorecard. The Gerber method was used for the determination of MC fat%. The mean counts of staphylococci [colony forming unit (CFU)/gm], coliforms (most probable number/gm), fungi (CFU/gm), and mesophilic bacteria (CFU/gm) were estimated in different fortified cheeses. Also, mean counts of Escherichia coli O157 and Staphylococcus aureus in artificially contaminated MC were determined. Results: The microbial xanthan (MX) had a significant (p < 0.05) effect on the sensory parameters of the examined samples with its concentration (0.0007%) after 20 days of storage. The MX (0.0005%) and CX (0.0002%) had a significant effect on moisture, fat in dry matter, and protein percentage of MC throughout the storage period. The high meltability degree of MC was observed in samples with both types of xanthan (0.0002%) at the end of storage. Conclusion: Both types of xanthan at all concentrations had a significant reducing effect on E. coli O157 and S. aureus in all samples from 10 to 30 days of storage. Xanthan has accepted attentiveness and offers beneficial and safe characteristics that improve its adaptability in MC. In the Middle East, this survival trial of E. coli O157 and S. aureus in the MC supplemented by xanthan is considered a scarce exploratory investigation.J. Adv. Vet. Anim. Res., 10(3): 469–483, September 2023http://doi.org/10.5455/javar.2023.j700